THE ROLE OF THE TEXTBOOK IN PROMOTING ENVIRONMENTAL EDUCATION VALUES AMONG FIFTH-GRADE PRIMARY PUPILS IN ALGERIA - Elbouche Zina; Latreche Halima (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to explore the role of the Science and Technology textbook in fostering environmental education values among fifth-grade primary school pupils in Algeria. The research employed a descriptive-analytical approach through a content analysis of the Science and Technology textbook used in the fifth grade. The findings revealed that the textbook contributes to the development of environmental education values to varying degrees, with percentages of 49.54%, 28.19%, and 22.25%, respectively. The cognitive domain ranked first in terms of emphasis, followed by the affective domain in second place, and finally the psychomotor domain, which ranked third.